(3KbGaI GdefXeI (B/s - (3GdNaGLj, fYeI YHGSs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3acQI Yf KbGaI GdefXeI h OhQgG aj JMbjb GdfLGM h GdJejR , feGPL KbGaI GdefXeI h Jchjf gPg GdKbGaI , JZjjQ KbGaI GdefXeI h GdJWHjY GdGLJeGYj (B.s
(3eQGLY U(B.145s
Keywords: (3GdGOGQIs; (3GdJWHjY GdELJeGYjs; (3GdefXeIs